On factors of consumer heterogeneity in (mis)valuation of future energy costs: Evidence for the German automobile market - Vlada Pleshcheva; Daniel Klapper; Till Dannewald (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
In this paper, we first recover the individual valuation of expected future fuel costs at the time of a car purchase and then explore how various factors relate to the recovered consumer undervaluation of fuel savings (on average, consumers' willingness-to-pay for a AC1 reduction in fuel costs is below AC0.20). For this purpose, we use survey data on the individual purchases of new passenger cars in Germany over seven years and use the expected driving intensity and the expected length of car ownership as stated by consumers to construct individual values of the present-discounted fuel costs. We then compare the variation in these values to that in the prices paid by buyers of cars with identical specifications. Individual tastes for car attributes are recovered nonparametrically within a "preference inversion" procedure for diesel and gasoline vehicles of various car classes, controlling for unobservable product attributes, correlations in tastes for car features, and the possibility to deduct a portion of annual fuel costs from taxes. Our results indicate that consumers' better financial ability, higher education, and brand loyalty facilitate a better understanding of the benefits of investments in fuel-efficient vehicles.
Keywords: D12; D90; M31; Q51; 330; Energy-efficiency paradox; hedonic discrete choice model; vehicle purchase; willingness-to-pay